A study of Ted Hughes's Birthday letters - Highman, Kathryn Barbara (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2004)
This thesis focusses on the literary self-reflexivity of Birthday Letters, Ted Hughes's collection of poems addressed to his long-dead first wife, poet Sylvia Plath. By close attention to the language of select poems and a discussion of cross-referencing images and allusions across the volume, and intertextually, I argue that the collection is more self-consciously ordered and designed than the mainly biographical criticism the work has met with suggests. The thesis focusses on the poets' art rather than the biographical context of Birthday Letters, though it does not draw a neat distinction between their lives and their poetry - rather it demonstrates how Birthday Letters itself treats the relationship of art to life thematically. The introduction outlines the context of the volume's genesis and publication and the notions of poetry, myth and drama out of which Hughes works, and introduces the central metaphor of metamorphosis as figured in Ariel's song "Full Fathom Five" from The Tempest, as well as the importance of that play to Plath. Each of the chapters that follow focusses on a cluster of inter-related imagery through a discussion of four or five key poems. Chapter One examines Hughes's portrayal of himself as imprisoned by Plath's poetic portraits, and relates this to the recurring motifs of the snapshot and the Medusa myth. The poems discussed emphasize Hughes's consciousness of the metamorphic and "magical" relationship of art to life. The second chapter discusses Hughes's use of the myth of the labyrinth and the Minotaur, tracing it back to Plath's writings and reading, and pointing out its self-reflexivity: the labyrinth figures Hughes's own loss as well as the labyrinthine nature of writing. The third chapter considers the themes of possession and loss, and how they attach themselves to images of houses and jewels. Possession and loss tum, self-reflexively, upon issues of inheritance and remembrance, notably Hughes's inheritance of Plath's poetic legacy, and his remembrance of her and her poetry through his own poetry. The conclusion pursues connections between the observations made in the separate chapters, outlining the larger context out of which the poems emerge, and returning to the trope of metamorphosis as figured in "Full Fathom Five"
Keywords: Hughes, Ted, 1930-1998 -- Criticism and interpretation; Hughes, Ted, 1930-1998 -- Birthday Letters